Trace regularization problem for a fourth-order differential operator on separable Banach space - Baksi, Ozlem; Sezer, Yonca; Caliskan, Seda Kizilbudak (WILEY, 2025)
In this study, we employ new results on the semi-inner product, the adjoint operator, and the Schatten class of operators on a separable Banach space, which allow us to investigate a differential operator with unbounded operator-valued coefficients. Specifically, we derive an asymptotic formula for the second regularized trace based on the asymptotic and spectral properties of the extended operator. For this purpose, we use the theory of continuous dense embeddings and known results regarding the regularized trace in Hilbert space. We conclude our paper by providing examples that support our findings.
Keywords: dense embedding; regularized trace; resolvent operator; separable Banach space; trace class operator; SPECTRAL THEORY; EIGENVALUES; ORDER; Mathematics